2004
DOI: 10.1126/science.1100618
|View full text |Cite
|
Sign up to set email alerts
|

A PINOID-Dependent Binary Switch in Apical-Basal PIN Polar Targeting Directs Auxin Efflux

Abstract: Polar transport-dependent local accumulation of auxin provides positional cues for multiple plant patterning processes. This directional auxin flow depends on the polar subcellular localization of the PIN auxin efflux regulators. Overexpression of the PINOID protein kinase induces a basal-to-apical shift in PIN localization, resulting in the loss of auxin gradients and strong defects in embryo and seedling roots. Conversely, pid loss of function induces an apical-to-basal shift in PIN1 polar targeting at the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
710
1
8

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 721 publications
(746 citation statements)
references
References 19 publications
27
710
1
8
Order By: Relevance
“…We propose the use of genes involved in cell polarization and early meristem formation to overcome this type of limitation. Polar auxin transport generates gradients that underlie the tropic growth response, leading to apical-basal patterning [11]. PINOID (PID) is a serine-threonine kinase that regulates auxin transport and is the major determinant of PINFORMED (PIN) protein localization (i.e.…”
Section: Esr1mentioning
confidence: 99%
See 3 more Smart Citations
“…We propose the use of genes involved in cell polarization and early meristem formation to overcome this type of limitation. Polar auxin transport generates gradients that underlie the tropic growth response, leading to apical-basal patterning [11]. PINOID (PID) is a serine-threonine kinase that regulates auxin transport and is the major determinant of PINFORMED (PIN) protein localization (i.e.…”
Section: Esr1mentioning
confidence: 99%
“…PINOID (PID) is a serine-threonine kinase that regulates auxin transport and is the major determinant of PINFORMED (PIN) protein localization (i.e. PIN1, PIN2 and PIN4) [11]. In shoot cells, where PID is normally expressed, PIN1 is located on the apical membranes, whereas in pid mutants, PIN1 is mistargetted to basal membranes [11]: constitutive expression of PID causes loss of meristem identity in the primary root.…”
Section: Esr1mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently it has been shown that TCH3 binds to PINOID (PID), a protein serine/ threonine kinase, in a yeast two-hybrid assay (Benjamins et al, 2003). PINOID had previously been shown to be necessary for proper auxin signaling (Bennet et al, 1996;Christensen et al, 2000) and a recent study suggests that it acts as a switch to regulate intracellular localization and the function of the PIN familu of auxin efflux regulators (Friml et al, 2004). TCH3 protein appears to bind PID and regulate the ability of the kinase to phosphorylate substrates in response to changing calcium ion levels (Benjamins et al, 2003).…”
Section: Touch and Gomentioning
confidence: 99%